Assessing caregiver stress and resource needs in pediatric cancer care - Shaimaa Mohamed Amin; Mahmoud Abdelwahab Khedr; Azza Medhat Aziz Mansy; Ahmed Hashem El-Monshed; Mohamed Gamal Noaman Malek; Ayman Mohamed El-Ashry (BMC Nursing)
Abstract Background Caregivers of pediatric cancer patients often face significant stress and emotional strain, which can negatively impact their well-being and the quality of care provided to their children. Understanding the socio-demographic factors influencing caregiver stress and identifying the specific needs and resources required by caregivers are crucial for improving support systems in pediatric cancer care. Aim of the study This study aimed to analyze the levels of caregiver stress and their resource needs within pediatric cancer care. Methods A cross-sectional descriptive design was used, and the study was conducted at El-Minia Oncology Center outpatient clinics, Egypt. The sample included 258 pediatric cancer caregivers selected based on predefined eligibility criteria. Data were collected using the Caregiver Needs and Resources Assessment (CNRA) and the King Stone Caregiver Stress Scale (KCSS), both of which demonstrated strong reliability and validity. Descriptive statistics, t-tests, ANOVA, and Pearson correlation coefficients were employed for data analysis using SPSS version 29, with a significance level set at p < 0.05. Results Caregivers reported moderate to high stress levels, with an average stress score of 34.59 (SD = 7.649). Age, education level, marital status, and income were significant predictors of caregiver stress (p < 0.001), with lower income and higher educational levels contributing to increased stress. The number of children, child’s age, and duration since cancer diagnosis also significantly impacted stress levels (p < 0.001). Correlation analysis revealed that psychological needs were positively related to stress (r = 0.488, p < 0.001), while spirituality was negatively associated with stress (r = -0.241, p < 0.001). Regression analysis indicated that physiological needs (ß = 0.331) and role conflict (ß = 0.294) were the strongest predictors of stress (R² = 0.636). Conclusion and implications This study emphasizes the impact of socio-demographic factors on caregiver stress in pediatric cancer care. Targeted interventions that address caregivers’ psychological, social, and financial needs are essential to alleviate stress. Implementing caregiver-centered support programs in pediatric oncology can enhance the well-being of both caregivers and patients. Future research should explore sustainable strategies to further reduce caregiver burden. Clinical trial number Not applicable.